Diagnostic study to Bovine Theileriosis by using PCR technique - Mohammed H. Khudor; Ghazi Y. A. Al-Emarah; Haider Rsheed Alrafas (Basrah Journal of Veterinary Research)
The present study performed in 51 cows from different age, sex and breed. The blood examination of all these animals showed high level of parasitemia varied between 17-52% and observed all parasite stages. The genomic diagnosis showed a high specificity and sensitivity to whole blood PCR test for diagnosis Theileria annulata moreover recorded a high percentage of infection by Theileria annulata 88.23% and lower percentage of infection 11.76% by other Theileria spp.